(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The rapid synthesis of 3-[4-(1,3-benzoxazol-2-yl)phenyl]-2-aryl-1,3-thiazolidin-4-one 4(a-h) was achieved through microwave-assisted methods. This involved the reaction of Schiff bases derived from 2-(4-amino phenyl) benzoxazole 3(a-h) with ethanol, SHCH2COOH (thioglycolic acid) (1 mol, 0.92 mL), and ZnCl2 (5 mol%) under microwave irradiation (400W, 146°C) for 3-4 minutes, resulting in excellent yields. Compound precursors 3(a-h) were prepared from aromatic aldehydes and 2-(4-amino phenyl) benzoxazole in ethanol, followed by microwave irradiation for 1-2 minutes, with reaction progress monitored via TLC. The expeditious reaction time is a notable advantage of this protocol. Comprehensive structural elucidation of the synthesized compounds involved elemental analysis, IR, NMR, 13C NMR, and Mass spectroscopy. These newly synthesized compounds, 4(a-h), were subjected to in vitro antimicrobial screening against Staphylococcus aureus, Escherichia coli, and antifungal screening against Aspergillus Niger. The zone of inhibition in millimeters was measured using the cup plate method. Several compounds within the series exhibited substantial activity when compared to the standard drugs streptomycin and Fluconazole.